2016
DOI: 10.3390/ijms17081244
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid A, as a Novel ETA Receptor Antagonist, Shows Inhibitory Effects on Tumor in Vitro

Abstract: Endothelin-1 (ET-1) autocrine and paracrine signaling modulate cell proliferation of tumor cells by activating its receptors, endothelin A receptor (ETAR) and endothelin B receptor (ETBR). Dysregulation of ETAR activation promotes tumor development and progression. The potential of ETAR antagonists and the dual-ETAR and ETBR antagonists as therapeutic approaches are under preclinical and clinical studies. Salvianolic acid A (Sal A) is a hydrophilic polyphenolic derivative isolated from Salvia miltiorrhiza Bung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Sal-A also inhibits AGE (advanced glycation end products)-induced endothelial cell injury [109] . A more recent study has shown that Sal-A is a safe ET1 type A receptor (ET A R) antagonist in HEK293 cells overexpressing ET A R (IC 50 =5.7 µmol/L) [113] , suggesting that Sal-A could have therapeutic effects in hypertension-associated vascular remodeling. Sal-A does not affect basal endothelial cell proliferation and NO production, but it reduces Ang II-induced proliferation of human endothelial cells by inhibiting ROS generation as well as blocking the phosphorylation of Src and Akt [114] .…”
Section: Effects Of Sal-a On Endothelial Dysfunction and Vascular Remmentioning
confidence: 99%
“…Sal-A also inhibits AGE (advanced glycation end products)-induced endothelial cell injury [109] . A more recent study has shown that Sal-A is a safe ET1 type A receptor (ET A R) antagonist in HEK293 cells overexpressing ET A R (IC 50 =5.7 µmol/L) [113] , suggesting that Sal-A could have therapeutic effects in hypertension-associated vascular remodeling. Sal-A does not affect basal endothelial cell proliferation and NO production, but it reduces Ang II-induced proliferation of human endothelial cells by inhibiting ROS generation as well as blocking the phosphorylation of Src and Akt [114] .…”
Section: Effects Of Sal-a On Endothelial Dysfunction and Vascular Remmentioning
confidence: 99%
“…Salvianolic acid A (SAA) is one of the most bioactive components extracted from Salvia miltiorrhiza Bunge (Danshen), a traditional Chinese herbal medicine with anti‐inflammation, antiplatelet, antihypertension, antithrombosis, antioxidation, and antirenal disease activities, as well as cardioprotective effects on myocardial infarction . Moreover, in recent years, SAA has been shown to possess other antitumor properties, including suppressive effects on tumor proliferation through targeting endothelin A receptor in DU145 cells and on the lung cancer multidrug resistance gene MDR1 through regulating microRNA expression . SAA could induce apoptosis and reduce c‐met expression by targeting the AKT/mTOR signaling pathway in lung adenocarcinoma cells .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in other cells such as HEK293/ETAR cell line, human mesenchymal stem cells and neuronal cells revealed that the inhibitory effect of SAA, SAB, and SAC had a minor effect on cells viability. [28][29][30] In this study, at concentrations greater than 200 μM, only SAA showed ACE2 h cytotoxicity and decreases cell viability. Moreover, the concentrations we chose in our experiment were below the toxic dose.…”
Section: Discussionmentioning
confidence: 54%